Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
(3, 3)
Step-by-step explanation:
do you need to show your work or just the answer?
-3x+7y=12 mulitply both sides by 3 of the bottom.
x-2y=-3
-3x+7y=12
3x-6y=-9 < which turns into this
Then you have to sum the equations (vertically) to eliminate one variable.
y=3
Then substitute the given value of "y" into the equation
x-2 * 3=-3 then solve the equation for x (x=3)
y=3 x=3 (3, 3)
*Check your answers.
-3*3+7*3=12
3-2*3=-3
12=12
-3=-3
(-3, -3)
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.